2013
DOI: 10.1160/th12-08-0584
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association studies of ACE and PAI-1 genes in women with recurrent pregnancy loss

Abstract: SummaryA fine balance between coagulation and fibrinolysis is critical in early pregnancy. Plasminogen activator inhibitor-1 (PAI-1) and angiotensin converting enzyme (ACE) are involved in the fibrinolytic process, and several studies have reported the association between their gene polymorphisms and recurrent pregnancy loss (RPL). This study was conducted to investigate the association between PAI-1 and ACE polymorphisms and idiopathic RPL, using meta-analyses. A systematic review of the published literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 38 publications
7
64
2
3
Order By: Relevance
“…In a previous study, Su et al 36 did not observe any association between the PAI-1-675G/A polymorphism and RPL based on 1545 cases and 960 controls. Moreover, Parveen et al 23 reported a null association between the -675G/A polymorphism and RPL risk based on 868 cases and 627 controls, which was not consistent with the present results of our meta-analysis.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, Su et al 36 did not observe any association between the PAI-1-675G/A polymorphism and RPL based on 1545 cases and 960 controls. Moreover, Parveen et al 23 reported a null association between the -675G/A polymorphism and RPL risk based on 868 cases and 627 controls, which was not consistent with the present results of our meta-analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Heritable hypofi brinolysis, mediated by 4G/4G homozygosity for the PAI-1 gene, may be associated with late placenta-mediated pregnancy complications, postulated to be through thrombotic induction of placental insuffi ciency [ 69 ]. A meta-analysis of the PAI-1 4G/5G polymorphism showed no associations with two or three pregnancy losses [ 70 ].…”
Section: Heritable and Acquired Thrombophilia In Assisted Conceptionmentioning
confidence: 99%
“…This multifunctional protein plays a key role in processes such as regulation of blood pressure, maintain a balance of electrolytes, platelet activation and aggregation, fibrinolysis. ACE protein functionality and features of its expression, associated with the presence of Alu-sequences in the intron, are devoted to a great number of publications [55,56,[60][61][62]. Virtually all studies agree that the presence of variant D (Del), lack of Alu-sequences in the intron of the ACE gene, is associated with atherosclerotic, cardiovascular disorders and the risk of pregnancy violation [29,61,62].…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 99%
“…ACE protein functionality and features of its expression, associated with the presence of Alu-sequences in the intron, are devoted to a great number of publications [55,56,[60][61][62]. Virtually all studies agree that the presence of variant D (Del), lack of Alu-sequences in the intron of the ACE gene, is associated with atherosclerotic, cardiovascular disorders and the risk of pregnancy violation [29,61,62]. At the molecular level, Alu insertion reduces the gene expression level that is displayed as s decrease in the level of ACE protein in the blood and more precise regulation of blood pressure without pronounced spikes as a consequence.…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 99%